Selective blockade of CD28 on human T cells facilitates regulation of alloimmune responses - Zaitsu, M; Issa, F; Hester, J; Vanhove, B; Wood, K (American Society for Clinical Investigation, 2017)
T cells are central to the detrimental alloresponses that develop in autoimmunity and transplantation, with CD28 costimulatory signals being key to T cell activation and proliferation. CTLA4-Ig molecules that bind CD80/86 and inhibit CD28 costimulation offer an alternative immunosuppressive treatment, free from some of the chronic toxicities associated with calcineurin inhibition. However, CD80/86 blockade by CTLA4-Ig also results in the loss of coinhibitory CTLA4 signals that are critical to the regulation of T cell activation. Here, we show that a nonactivating monovalent anti-CD28 that spares CTLA4 signaling is an effective immunosuppressant in a clinically relevant humanized mouse transplant model. We demonstrate that selective CD28 blockade prolongs human skin allograft survival through a mechanism that includes a reduction in the cellular graft infiltrate. Critically, selective CD28 blockade promotes Treg function in vivo and synergizes with adoptive Treg therapy to promote transplant survival. In contrast to CTLA4-Ig treatment, selective CD28 blockade promotes regulation of alloimmune responses and facilitates Treg-based cellular therapy.